2017
DOI: 10.1055/s-0043-119751
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Flaxseed Oil Omega-3 Fatty Acids Supplementation on Metabolic Status of Patients with Polycystic Ovary Syndrome: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Overall, flaxseed oil omega-3 supplementation for 12 weeks in women with PCOS had beneficial effects on insulin metabolism, mF-G scores, serum triglycerides, VLDL-cholesterol and hs-CRP levels, but did not affect hormonal and other lipid profiles, and plasma nitric oxide levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 37 publications
1
61
0
2
Order By: Relevance
“…Of the 80 trials identified that used mineral oil, 16 reported high-sensitivity C-reactive protein (hsCRP) levels ranging from −15.9% to +33.3%; levels were increased in 10 studies, 8 , 40 , 42 , 53 , 55 , 56 , 62–64 decreased in 5 studies, 47 , 50 , 61 , 65 , 66 and unchanged in 1 study. 67 As with lipid parameters, most changes were inconsistent and not reported as statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 80 trials identified that used mineral oil, 16 reported high-sensitivity C-reactive protein (hsCRP) levels ranging from −15.9% to +33.3%; levels were increased in 10 studies, 8 , 40 , 42 , 53 , 55 , 56 , 62–64 decreased in 5 studies, 47 , 50 , 61 , 65 , 66 and unchanged in 1 study. 67 As with lipid parameters, most changes were inconsistent and not reported as statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Serum insulin concentration was determined by using ELISA kits (Dia plus, Canada) with inter-and intraassay CVs of less than 12% and less than 10%, respectively. IR was determined by HOMA-IR using the following formula: HOMA-IR = [fasting insulin (mU/L) × fasting blood glucose (mg/dL)] / 405 [1]. Insulin sensitivity was also calculated by QUICKI equation: QUICKI = 1 / [log (fasting insulin, lU/mL) + log (fasting glucose, mg/ dL)] [1].…”
Section: Biochemical Analysismentioning
confidence: 99%
“…IR was determined by HOMA-IR using the following formula: HOMA-IR = [fasting insulin (mU/L) × fasting blood glucose (mg/dL)] / 405 [1]. Insulin sensitivity was also calculated by QUICKI equation: QUICKI = 1 / [log (fasting insulin, lU/mL) + log (fasting glucose, mg/ dL)] [1]. Serum total testosterone with inter-and intraassay CVs of 9.7 and 4.8% was determined by using direct immunoenzymatic assay (Accu Bind, USA).…”
Section: Biochemical Analysismentioning
confidence: 99%
See 2 more Smart Citations